Efficiency droop in nitride-based light-emitting diodes - Piprek, Joachim (Physica status solidi. A, Applications and materials science, 2010)
Nitride‐based light‐emitting diodes (LEDs) suffer from a reduction (droop) of the internal quantum efficiency with increasing injection current. This droop phenomenon is currently the subject of intense research worldwide, as it delays general lighting applications of GaN‐based LEDs. Several explanations of the efficiency droop have been proposed in recent years, but none is widely accepted. This feature article provides a snapshot of the present state of droop research, reviews currently discussed droop mechanisms, contextualizes them, and proposes a simple yet unified model for the LED efficiency droop. Illustration of LED efficiency droop (details in Fig. 13).